A formação do leitor no âmbito da educação profissional e tecnológica: desafios e possibilidades - Oliveira, Maria Cristina Rodrigues (2021)
This dissertation discusses the process of reader training for Professional and Technological Education students at the Piemonte Territorial Center of Diamantina II (CETEP), located in the city of Jacobina-BA. Concerns arising from dialogues with teachers working in Professional and Technological Education regarding the reading skills of students in technical courses and the difficulty of involving students in the reading practices proposed in these courses mobilized this research, which launches reflections on pedagogical actions of reading implemented by teachers of the technical courses. The general objective is to understand how the student reading training process is constituted in the scope of Professional and Technological Education, in the Territorial Center of Piemonte da Diamantina II (CETEP). To this end, the CETEP Technical Course in Informatics is taken as an empirical space, identified by teachers as the one with the highest rate of students with reading difficulties and also because it is the one with the least involvement by students, in events and projects. school and also in large-scale assessments, such as the Bahian Education Assessment System (SABE). In the theoretical field, this research is based on the axes Professional and Technological Education, Teacher Training and Reading.From them, categories such as integral formation, permanent formation, conceptions of reading and reader and pedagogical actions of reading unfold. Of a qualitative nature, in the methodological field, the study is guided by the collaborative research approach. The data were produced in dialogue with the research collaborators, namely, five CETEP professors, through the semi-structured interview and discussion group devices. The methodology used for the interpretative analysis of the data is anchored in the Discursive Textual Analysis (ATD), which allows the researcher to construct meanings based on inferences in the texts and in the contexts in which they were produced. The results allowed to infer that there is a teaching work in progress that aims at the formation of a critical and autonomous reader in the Technical Course in Informatics at CETEP; however, there is still a need for a consistent proposal to be taken on by the whole school, which provides systematic, interdisciplinary pedagogical reading actions, based on the diversity of local and global cultures and the diversity of languages, with an emphasis on human and professional training of subjects protagonist readers of contemporary society.